2019
DOI: 10.2478/jomb-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide products are not associated with metabolic syndrome

Abstract: Summary Background Nitric oxide (NO) is oxidative stress biomarker which is regarded as one of the key determinants of energy metabolism and vascular tone. Considering the controversial reports on the association between nitric oxide products (NOx) and metabolic syndrome (MetS), the aim of the current study was to examine that potential relationship. Additionally, we aimed to evaluate a broad spectrum of other oxidative stress biomarkers [i.e., malondialdehyde (MDA), advanced oxidation protein products (AOPP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
3
15
1
1
Order By: Relevance
“…Similar results were reported by other authors who found no statistical differences in NO levels in obesity. 48,49 Furthermore, it is described that the capacity of the endothelium to release NO under basal conditions is not compromised in overweight and obese adults. 50 Adipocytes secrete TNF-α and IL-6, and their concentration is associated with the percentage and distribution of adipose tissue in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by other authors who found no statistical differences in NO levels in obesity. 48,49 Furthermore, it is described that the capacity of the endothelium to release NO under basal conditions is not compromised in overweight and obese adults. 50 Adipocytes secrete TNF-α and IL-6, and their concentration is associated with the percentage and distribution of adipose tissue in the body.…”
Section: Discussionmentioning
confidence: 99%
“…According to available literature, NO may be involved in the initiation of LPO (34) by many putative ways, NO a donor of S-nitroso-N-acetyl penicillamine (SNAP) in U937 cells can inhibit glutathione peroxidase that leads to increased levels of lipid peroxidation (34). Another way is the reaction of NO with molecular oxygen generates a radical-radical combination of product nitrogen dioxide (•NO 2 ), which can initiate lipid peroxidation (8).…”
Section: Discussionmentioning
confidence: 99%
“…It has a great capability of diffusion between body tissues and performs several important biological functions such as vasodilatation, modulation of nociception, immune function, neurotransmission, and excitation-contraction coupling (6,7). NO a free radical signal-transuding agent, has been shown to undergo a sequence of reactions, leading to the generation of reactive nitrogen species (RNS) in a variety of cells (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this balance, the damage to the organism by the free radicals is prevented. The imbalance between free radical production and the antioxidant defence system for free radicals is called the »oxidative stress« (7,8) Total antioxidant status (TAS) reflects the total effect of all antioxidants, and total oxidant status (TOS) reflects the total effect of all oxidants in plasma and body fluids (7,9,10). Paraoxonase 1 (PON1) is a serum esterase and the most known member of the paraoxonase multigene family (11).…”
Section: Introductionmentioning
confidence: 99%